Hydroponic NFT agricultural monitoring website: Temperature control based on PID - Wahyuni Sri; Rusydi Amin; Fuad Muhammad (BIO Web of Conferences)
This study aims to develop an automated control system for hydroponic growing media to optimize temperature and nutrient conditions tailored to various plant types. The control method proposed in this study uses the Proportional Integral Derivative (PID). PID control allows for precise adjustments in temperature and nutrient levels, enhancing plant growth. A web-based interface enables users to monitor and adjust the system settings according to their chosen plant type. The vegetables planted for the trial testing of this system are caisim, pok choy, spinach, lettuce, broccoli, and cauliflower, which can grow in lowlands and highlands. Users will also get a reminder of the estimated harvest of plants being planted through the monitoring website so that users do not have to bother calculating the length of the planting process. The system achieves a remarkable control accuracy of 99.9% in maintaining optimal conditions, although it struggles to cool water to the desired 25℃ during peak daytime temperatures. This is because the Peltier work is very dependent on the ambient temperature. Future research may explore alternative cooling methods or adjustments to the Peltier for a more efficient cooling process or continue to use the Peltier but think about a better heat exchange concept in both the heat exchanger water so that the hot water resulting from the cooling process using the Peltier does not settle in one container. It is expected to make it easier for someone to grow vegetables for food-oriented development (FOD) and urban farming.